The isolation of lexical item ‘tea’ from ‘spill the tea’ among Malay twitter users - Hamdi Khalis; Hibriyatul Rifhan (Penerbit Universiti Kebangsaan Malaysia, 2019)
The appropriation of idioms in everyday communication has been a norm among language users. Lately, the use of only a single lexical item in an idiomatic phrase has been widely used especially by social media users. The use of isolated lexical item ‘tea’ from ‘spill the tea’ has been used extensively by Malay Twitter users. This research looks into the contexts that motivate Malay Twitter users to use the isolated lexical item ‘tea’. Thematic analysis was used as the framework of this research in order to strategically identify the context of this phenomenon. There are five categories in which the contexts fall into; 1) revealing oneself own secret, 2) workplace related issue, 3) Celebrity Gossips, 4) revealing another people’s secret, and 5) political discussion. The analysis revealed that most users used the isolated lexical item ‘tea’ when the users wanted to unveil a secret. Besides that, it is worth noting that even on social media, Malay users tend to avoid criticising a threatening issue. The findings of this research can be further applied in analysing the appropriation of idioms among social media users.